2016
DOI: 10.1063/1.4955196
|View full text |Cite
|
Sign up to set email alerts
|

Predictive coupled-cluster isomer orderings for some SinCm (m, n ≤ 12) clusters: A pragmatic comparison between DFT and complete basis limit coupled-cluster benchmarks

Abstract: Predictive coupled-cluster isomer orderings for some Si n C m (m, n ≤ 12) clusters; A pragmatic comparison between DFT and complete basis limit coupled-cluster benchmarks.Jason N. Byrd, 1, 2, a) Jesse J. The accurate determination of the preferred Si 12 C 12 isomer is important to guide experimental efforts directed towards synthesizing SiC nano-wires and related polymer structures which are anticipated to be highly efficient exciton materials for opto-electronic devices. In order to definitively identify pref… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 125 publications
1
21
0
Order By: Relevance
“…Functionals such as B3LYP, M11 or PBE0 attempt to compensate for the above mentioned shortcomings of typical GGA/LDA functionals. The recent extensive benchmark study by Byrd et al (2016) confirms that the M11 functional is able to correctly identify all investigated (SiC) n ground states. Although B3LYP (Becke 1993) was found to be less accurate than M11 for SiC clusters, we also include data calculated with this widely used functional for comparison.…”
Section: Quantum-mechanical Refinementmentioning
confidence: 69%
“…Functionals such as B3LYP, M11 or PBE0 attempt to compensate for the above mentioned shortcomings of typical GGA/LDA functionals. The recent extensive benchmark study by Byrd et al (2016) confirms that the M11 functional is able to correctly identify all investigated (SiC) n ground states. Although B3LYP (Becke 1993) was found to be less accurate than M11 for SiC clusters, we also include data calculated with this widely used functional for comparison.…”
Section: Quantum-mechanical Refinementmentioning
confidence: 69%
“…Geometry optimizations are accellerated significanty by parallel implementations leveraging analytic gradients. In a previous study we have investigated the relative performance of a variety of DFT, MP2, and highlevel CC methods for producing geometries of several Si n C m (n ≤ m ≤ 12) molecules [66], which are expected to exhibit similar many-body physics to defects in solidstate SiC. The previous study found that MP2 and DFT with the M11 functional were good alternatives, which could closely reproduce the geometries predicted by highlevel SRCC methods.…”
Section: Computational Detailsmentioning
confidence: 99%
“…Some TD-DFT calculations are included for comparison, but benchmarking various functionals is outside of the scope of this work so we use those deemed optimal for Si n C m (n ≤ m ≤ 12) molecules in Refs. [66] and [67] (see Sect. III for further details).…”
Section: Introductionmentioning
confidence: 99%
“…For larger sizes of mixed Si-C clusters, Zhu et al [17] investigated the growth patterns and electronic property of Si12C12 clusterassembled materials. In addition, by using the DFT and the coupled-cluster theory, some SinCm (m, n ≤ 12) clusters ranging in size from SiC3 to Si12C12 were predicted [18]. Most recently, silicon impacts on structure, stability and aromaticity of C20-nSin heterofullerenes (n = 1 -10) were studied in a density functional perspective [19].…”
Section: Introduction mentioning
confidence: 99%